Community Contacts: Being Prepared for a Disaster - Linda B. Bobroff (EDIS)
When a disaster strikes, it’s too late to get ready. It’s important to prepare for a disaster before an emergency occurs. Along with the information provided in this series, the agencies listed can help you be well prepared to handle just about any emergency. The time to get ready is NOW, so call the agencies for information or, if you have Internet access, look at the websites and print out what you need. Put together your disaster kit and your disaster plan BEFORE you need it. This document is FCS9190, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: May 2003.